Adolescent Between the Two Shores. Presenting Case of Psychotherapeutic Practice - Stefanka Tomcheva (The Global Psychotherapist, 2021)
A case of psychotherapeutic practice for an adolescent between identity, symptom and balance. Individual identity is essential for mental health. Identity development is a basis of self-acceptance and good self-esteem. As Erikson (2013) pointed out, subjective sense of identity must continue to be rediscovered and developed in a never-ending process. Erikson emphasizes that the term of identity has different but generally interrelated meanings. In many situations it can be attributed to a conscious sense of individual identity, in the others – to “an unconscious battle” for continuity between tradition and individuality, in the third – to the stability of the self, and in the fourth – as a mechanism for maintaining internal balance with group (traditional) ideals and group (traditional) identity